Approaching the perception of pedagogy graduates about their initial teacher training in Magallanes, Chile (Revista Electrónica Diálogos Educativos. REDE, 2019)
Initial Teacher training is one of the primary foundations for the improvement of education in general terms, since teacher preparation will influence the results of future learners. Teacher's perception has not been considered as an object of evaluation for their own educational process, and that is the reason why elaborating a study based on their experiences was considered relevant. The following study is based on the gathered information about the teacher’s perception in Punta Arenas and Puerto Natales regarding their preparation, all as a first approach on this issue in Magallanes. Data and information were collected through a self-applied survey, whose main idea was the general portrayal of the training process. Concerning the results, it was perceived that teachers from all the three levels of education assess positively the theory and practicum of their alma mater, in spite of the low results they delivered about ICT (Information and Communication Technologies). Regarding the educational institution, results are categorical in establishing those which are from the private area higher in the ranking as the best evaluated by their graduated students. Finally, those teachers with a career of less than fifteen years, tend to be more critical about the infrastructure of their educational institutions, in spite of having better accessibility to their buildings, better tools and furniture that directly benefit the learning process. Thanks to this study it was possible to conclude that the assessment of the graduates through the perception of their own learning and formative process, is a highly important input, especially when it comes to generate new public policies that directly benefit future teachers.